ANALYSIS OF BENEFITS AND CHALLENGES IN MINIMALLY INVASIVE PEDIATRIC SURGERY BASED ON THE PRISMA METHODOLOGY - Hoshchynskyi, P.V.; Migenko, B.O.; Drosyk, M.M.; Mykolenko, A.Z.; Golovata, T.K.; Dzhyvak, V.H.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the current status and future potential of minimally invasive surgery in pediatric practice, focusing on its application in congenital anomalies and pediatric oncology, and explores the benefits, challenges, and advances in minimally invasive surgery, with an emphasis on laparoscopic and thoracoscopic techniques. This review explores their current applications and future potential in treating congenital anomalies and pediatric cancers. A systematic analysis of studies from 2009 to 2024, drawn from major medical databases, highlights the advantages of laparoscopic and thoracoscopic approaches, including shorter hospital stays, reduced tissue damage, and improved cosmetic results. The authors stress that minimally invasive techniques are increasingly used in pediatric surgery for their ability to minimize trauma and accelerate recovery. They indicated the challenges are still present such as the requirement for specialized tools, high technical expertise, and the anatomical complexity of young patients. The review also examines emerging technologies like robotic-assisted systems and artificial intelligence, which may enhance surgical precision and patient safety. ption in pediatric practice can occur. The basic conclusion is done that minimally invasive surgery will become more accessible and effective for paediatrics with modern technology development and additional clinical researches.
Keywords: pediatric surgery; laparoscopy; thoracoscopy; robotic surgery; pediatric oncology; congenital anomalies